Optimization of ovarian function and metabolic status in syndrome of polycystic ovaries - Т. Ф Татарчук; Н. В. Косей; Т. М. Тутченко; М. І. Гламазда (Publishing House TRILIST, 2020)
Objective: to evaluate the effect of the Quinofolic complex (myo-inositol 500 mg, D-chiro-inositol 12.5 mg, methyltetrahydrofolate 250 mcg) on ovarian function, metabolic status and biochemical hyperandrogenism in women with classic phenotypic phenotype of polycystic ovary syndrome (PCOS) and insulin resistance. Materials and methods. An open comparative study was conducted in 60 women of early/active reproductive age diagnosed with PCOS (classic phenotypic form) and laboratory confirmed insulin resistance, divided into 2 groups: study group received recommendations for lifestyle modification in accordance with clinical guidelines 2018, as well as Quinofolic in a dose of 2 capsules per day; control group received similar recommendations for lifestyle modification and folic acid, similar to the one in Quinofolic for 6 months. End points of the study were: duration of intermenstrual intervals and ultrasonographic signs of ovulation; dynamics of HOMA index, waist/hip ratio, free testosterone index. Results. At the end of the third month of treatment statistically significant reduction of intermenstrual intervals was recorded in the study group: 45.6 ± 3.2 vs 68.9 ± 8.2 days before treatment. At the end of the sixth month of treatment, the average duration of intermenstrual intervals in the study group was 32.6 ± 2.8 days. Also, the average duration of intermenstrual intervals in the study group differed statistically significantly from the control group: 45.6 ± 3.2 vs 68.2 ± 5.6 days at the end of the 3rd month and 32.6 ± 2.8 vs 56.6 ± 4 8 days at the end of the sixth month. Average duration of intermenstrual intervals in the control group at the end of the third month did not show statistically significant dynamics. The dynamics of waist/hip ratio decrease in the study and control groups was comparable, but these changes were not statistically significant compares to values before the intervention in both groups. At the same time in the study group, a statistically significant decrease of HOMA index and free testosterone index were recorded synchronously with a decrease in waist/hip ratio. Despite the significant effect of lifestyle modification in individual participants in the control group, the average HOMA index and level of free testosterone index did not show statistically significant changes. Conclusions. Results of the study combined with data on the effectiveness of the combined use of inositol isomers myo-inositol/D-chiro-inositol ratio = 40:1 confirm the feasibility of their use to improve folliculogenesis, reduce hyperandrogenism and insulin resistance in women with PCOS.